2018
DOI: 10.1002/ps.4912
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and evolution of a chemosensory receptor gene family in three notorious rice planthoppers, Nilaparvata lugens, Sogatella furcifera and Laodelphax striatellus, based on genome and transcriptome analyses

Abstract: The results demonstrate the importance of the planthopper Orco genes in locating rice plants. This information may aid in the development of RNAi-based transgenic rice and other pest management technologies. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 106 publications
(201 reference statements)
4
39
0
Order By: Relevance
“…(A)–(C)). Notably, all three rice planthoppers displayed a ‘lack of response,’ during which they did not select rice plants or an air control after 1.5 h. The results were similar to those observed with Orco deficit in rice planthoppers and OBP3 deficit in BPH, which revealed that rice planthoppers with a single OBP deficit indeed lose the ability to seek rice plants and exhibit delayed selection.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…(A)–(C)). Notably, all three rice planthoppers displayed a ‘lack of response,’ during which they did not select rice plants or an air control after 1.5 h. The results were similar to those observed with Orco deficit in rice planthoppers and OBP3 deficit in BPH, which revealed that rice planthoppers with a single OBP deficit indeed lose the ability to seek rice plants and exhibit delayed selection.…”
Section: Resultssupporting
confidence: 77%
“…(A)–(C)). The results were similar to the Orco RNAi efficacy in these three rice planthoppers, suggesting that RNAi is a practical tool to study the olfactory genes in rice planthoppers.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…Recently, 141, 135 and 37 ORs were separately identified from three rice planthoppers, Nilaparvata lugens, Sogatella furcifera and L. striatellus, in which Orco is the most conserved and essential odorant receptor gene. 41 The highly conserved Orco is considered as a potential target for a disruption of olfactory signaling. Excitingly, several N-, 2-substituted triazolothioacetamide compounds (VUAA1, VU0450667 and VU0183254) were recently reported to act directly on Orco subunit of Anopheles gambiae, 42,43 suggesting that broadly active compounds can be developed.…”
Section: Discussionmentioning
confidence: 99%